Global Changes in the Economic System and in Communications: A Latin American Perspective for the Political Economy of Communications - Bolano, César; Mastrini, Guillermo; Sierra, Francisco (Javnost-The Public, 2004)
In the past few decades, there has been an accelerated and transversal change in the “techno-information mechanisms” of production and reproduction in modern society. This change belies a new cultural ecosystem whose configuration and organizational logic is clearly unstable and random. This has affected the cultural codes, the methods of configuration, representation of space and time, the habits and forms of interaction and public knowledge, the models of regulation and control of the networks and infrastructures of data transmission. The very roots of the relationship between capital, work, and knowledge have been altered. The unfolding of the digital revolution and the accelerated expansion of the media and industries of information and culture have not only served to alter the map of social communications systems, but also led to a profound transformation in the organizational system of public life. The authors emphasise the main intellectual predecessors that can contribute to a diagnosis and alternative transformation of the universe of communications. Thus we will establish a basis for a new critical viewpoint of the peripheral, dependent countries of Latin America and the international division of intellectual work in the context of computerization.